HOMESCHOOLING; An Alternative Islamic Education Institution in Muslim Family - Ilman Nafi'a; Septi Gumiandari (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2021)
ABSTRACTThis study aims to explain how homeschooling concept can be an alternative Islamic educational institution in the Muslim family. This study used qualitative methodology with a literature approach. The results showed that (1) Homeschooling is not a new issue in Islamic education. Rasulullah is an originator of homeschooling-based education. The education process was carried out by the Rasulullah at Arqam's house where Rasulullah educated many of his friends and gave birth to many students of extraordinary abilities; (2) There are 3 types of homeschooling in the Islamic tradition: single homeschooling (family), compound homeschooling (halaqah), and homeschooling communities (mosque); (3) Homeschooling based on fitrah education contains monotheism, religious, moral, leadership, and vocational educations; (4) There are seven aspects that must be a concern in family education such as faith, morals, physical, intellectual, psychological, social, and sexual aspects; and (5) To internalize these seven aspects of education, it is necessary to use several methods: education by examples, customs, giving advices, attentions, rewards and punishments.Key Words: Â Homeschooling, Family, and Islamic Education